CSC coupled Graham Kenney source term for hybrid models of BLEVE events: Formulation, implementation and validation. Issue 4 (10th March 2021) - Abdel‐Jawad, Madhat
Abstract: Boiling liquid expanding vapor BLEVE events are notoriously difficult to model. Recently a new approach has been suggested and implemented within the code exploCFD which employs a hybrid approach for the modeling of multiple types of explosions including BLEVEs. The general approach is that the results from an analytical model are fed as a source term into a CFD calculation to model the wider domain. Here we propose a new analytical model for the modeling of BLEVE events to be used within the framework of a hybrid approach. The base Graham Kenney source term model, which predicts the source maximum pressure, is modified and also coupled with the CSC gas explosion model to incorporate the capability to model the subsequent ignition of the fuel in a complex congested and/or confined environment. We test the model against several experiments and compare the key parameters of BLEVE events which are: the maximum overpressure, and the impulse and the time history of the first peak. The simulated predictions of these key parameters using this method are shown to far outperform previous CFD, analytical and hybrid models.